PENGARUH KEPUASAN KERJA, KOMPETENSI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) BHAKTI SUMEKAR SUMENEP - jurnalmap map; Ahmad Halim Shidiq; Wasis Budiarto; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep with a total sample of 150people. The objectives of this study are: 1). To describe the functional training, HR competencies, motivation and career development, 2). To analyze whether functional training, HR competency, and motivation have a simultaneous and significant effect on the career development, 3). To analyze whether functional training, HR competency, and motivation have a partial and significant influence on the career development, 4). To analyze which variables between functional training, HR competency, and motivation have a dominant and significant effect on the career development of employees of the marketing department of the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep. The results showed that the: 1). Simultaneously, HR Competence and Motivation had an influence on Employee Career Development in the Marketing Section, 2). Partially Functional Training, HR Competence and Motivation have an influence on Employee Career Development. Keywords: job satisfaction, competence, discipline and work achievement.